2016
DOI: 10.1159/000445167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin-Converting Enzyme Inhibitors in Contrast-Induced Nephropathy: A Meta-Analysis

Abstract: Aims: The purpose of this study was to evaluate the effect of angiotensin-converting enzyme inhibitors (ACEIs) on contrast-induced nephropathy (CIN) in patients undergoing coronary angiography or percutaneous coronary intervention (PCI). Methods: We searched the Medline, Embase, Cochrane Library, China National Knowledge Infrastructure, Chongqing VIP database and Wanfang database up to December 2014. Pooled risk ratios (RRs) or weighted mean difference (WMD) with their 95% CIs for the CIN incidence, serum crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…We think that, cessation of ACEI/ARB treatments for only 1 d before the procedure might not be adequate because renal hemodynamic effects of these drugs might last longer. In a very recent meta-analysis, ACEI use was not found to have a significant effect on the CI-AKI in patients undergoing PTCA[76]. In summary, there is not enough evidence to recommend withholding or continuing ACEI/ARB treatments before contrast-enhanced imaging.…”
Section: Prevention Of Ci-akimentioning
confidence: 99%
“…We think that, cessation of ACEI/ARB treatments for only 1 d before the procedure might not be adequate because renal hemodynamic effects of these drugs might last longer. In a very recent meta-analysis, ACEI use was not found to have a significant effect on the CI-AKI in patients undergoing PTCA[76]. In summary, there is not enough evidence to recommend withholding or continuing ACEI/ARB treatments before contrast-enhanced imaging.…”
Section: Prevention Of Ci-akimentioning
confidence: 99%
“…In recent years, 3 meta-analyses/systematic reviews were reported that examined the incidence of CIN in coronary angiography (CAG) (including arterioplasty). Zhou et al reported [18] that the incidence of CIN was 7.9% under the continuous administration of ACE inhibitors (control: 8.2%, RR 0.95, and 95% CI 0.57-1.58). Jo et al [19] reported that the use of RAS inhibitors was not a significant risk factor (OR 1.27, 95% CI 0.77-2.07, p = 0.351) in the meta-analysis.…”
Section: Level Of Evidence: Ii/grade Of Recommendation: Not Applicable Rationale Cq3-4mentioning
confidence: 99%
“…No data are available about protective or deleterious effects of Angiotenin converting enzyme (ACE) inhibitors and Angiotensin Receptor Blockers (ARBs) in patients undergoing a contrast-enhanced CT. Data from interventional procedures in patients with coronary disease, also showing conflicting results, 56,57 should not be taken as a paradigm. Theoretical favorable effects by means of Angiotensin converting enzyme 2 (ACE2)-mediated vasodilation and Angiotensin II (AT2) receptor mediated Nitric oxyde sinthase (NOS) upregulation may be counterbalanced by renal hypo-perfusion and reduction of glomerular filtration pressure, leading to detrimental effect on CIAKI occurrence in these patients.…”
Section: Prophylactic Measures To Prevent Ciakimentioning
confidence: 99%